Amino-fulleropyrrolidines as electrotropic additives to enhance organic photovoltaics. Issue 10 (8th August 2018) - Karak, Supravat; Page, Zachariah A.; Li, Shaoguang; Tinkham, Jonathan S.; Lahti, Paul M.; Duzhko, Volodimyr V.; Emrick, Todd
Abstract : The synthesis, device fabrication, and electric poling of novel amino-functionalized fulleropyrrolidines in polymer solar cells is reported. Significantly improved device performances and retention stability were achieved with systematic variation in tether length, reaching PCE values in excess of 10%. Abstract : The synthesis, device fabrication, and electric poling of novel amino-functionalized fulleropyrrolidines in polymer solar cells is reported. Systematically varying the tether lengths between the fullerene cage and tertiary amines provides insight into enhanced device efficiency and stability after poling. DFT calculations in an external electric field result in alignment of molecular dipole moments, which corroborates our hypothesis that electrotropic polarization causes an increased built-in electrostatic potential difference across the device, and results in enhance performance.